Pemberdayaan UMKM Melalui Pelatihan Pemasaran Digital Di Desa Karang Satria Tambun Utara Kabupaten Bekasi - Rizal, Moch.; Yuli, Rama; Rasenda, Rasendea; Wiyana, Hari; Ibarda, Aditya (PT. Riset Press International, 2025)
Digital marketing training is an important step in efforts to empower Micro, Small, and Medium Enterprises (MSMEs) to face business competition in the digital era. This community service program aims to improve the competence of MSME actors in Karang Satria Village, North Tambun District, Bekasi Regency, especially in utilizing digital media as a means of product marketing. The training is conducted with a practical and participatory approach, including introducing digital marketing platforms and content strategies and using digital applications that support sales. The results of the activity showed an increase in participants' understanding and skills in optimizing digital marketing, which had a positive impact on expanding market reach and increasing business turnover. These findings affirm the importance of digital marketing training as a means of empowering MSMEs to adapt and develop in the midst of information technology developments. It is suggested that there be further assistance to ensure the sustainability of the implementation of digital marketing strategies by MSME actors.